(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Proceedings of the 40th Scientific conference of the Physiological Society of Nigeria hosted by the Department of Physiology, College of medicine, Uiversity of Ibadan. Ibadan, Nigeria